2016
DOI: 10.3892/mmr.2016.5692
|View full text |Cite
|
Sign up to set email alerts
|

ZFAT gene variant association with multiple sclerosis in the Arabian Gulf population: A genetic basis for gender-associated susceptibility

Abstract: Single nucleotide polymorphisms (SNPs) are useful genetic markers to investigate the onset of multiple sclerosis (MS). A genome wide association study identified 7 SNPs associated with interferon-β therapy response, however, not with MS risk in a Spanish population. To investigate these findings in a different cohort, the 7 SNPs were investigated in an Arabian Gulf population. The SNPs were analyzed in 268 subjects (156 patients and 112 healthy volunteers) from the Arabian Gulf region using restriction fragmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
3
0
1
Order By: Relevance
“…ZFAT can recognize histone H3 acetylation, which is involved in inflammation-mediated epigenetic modulation of memory [30]; another target gene of ZFAT is bromodomain and PHD finger containing 1 [30], which is important for brain development [31] and is associated with schizophrenia [32]. Previous research has found that deficits in ZFAT were associated with autoimmune thyroid disease [33] and a ZFAT variant was associated with multiple sclerosis that sometimes involves memory deficits [34]. So far, its relationship with memory has not been well studied.…”
Section: Discussionmentioning
confidence: 99%
“…ZFAT can recognize histone H3 acetylation, which is involved in inflammation-mediated epigenetic modulation of memory [30]; another target gene of ZFAT is bromodomain and PHD finger containing 1 [30], which is important for brain development [31] and is associated with schizophrenia [32]. Previous research has found that deficits in ZFAT were associated with autoimmune thyroid disease [33] and a ZFAT variant was associated with multiple sclerosis that sometimes involves memory deficits [34]. So far, its relationship with memory has not been well studied.…”
Section: Discussionmentioning
confidence: 99%
“…However, ZFAT is expressed in B and T lymphocytes and has shown to be a critical transcription regulator involved in apoptosis and cell survival (Fujimoto et al, 2009). Bourguiba-Hachemi et al (2016) found that another variant, rs733254 , in ZFAT is a risk marker for multiple sclerosis (MS) in women. Multiple studies have also detected an association between ZFAT and the severity of autoimmune thyroid disease (Inoue et al, 2012; Sakai et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It should be mentioned that another study re-established the consistent paternal expression of ZFAT-AS1 in human placenta; the monoallelic expression of the ZFAT gene was also revealed, but random activity of either of the parental alleles [ 122 ]. It was in one of the genetic studies that the polymorphic variant rs733254 in ZFAT gene was associated with RRMS in women, but not in men, in an Arabian Gulf population (odds ratio 2.38 and 95% confidence interval 1.45–3.91; p = 0.0014) [ 123 ]. Genome-wide association study demonstrated the association of this variant with INF-β therapy response in MS patients [ 124 ].…”
Section: Imprinted Genes and Msmentioning
confidence: 99%